Synthesis, structure and magnetic properties of copper(II) complexes of 2-amino-5-trifluoromethylpyridine (5-TFMAP): (5-TFMAP)2CuX2 (X = Cl or Br), (5-TFMAP)3CuBr2 and [(5-TFMAP)2CuBr2](5-TFMAPH)Br. (29th March 2015) - Forman, R. Louise; Gale, Alexander J.; Landee, Christopher P.; Turnbull, Mark M.; Wikaira, Jan L.
Graphical abstract: Copper(II) chloride and bromide complexes of 2-amino-5-trifluoromethylpyridine (5-TFMAP) have been prepared and characterized structurally and magnetically [(5-TFMAP)2 CuX2, X = Cl, Br; (5-TFMAP)3 CuBr2 ]. The chloride complex is well modeled as an alternating antiferromagnetic chain while the tris-complex is well described as a uniform antiferromagnetic chain with moderate interactions ( J  = −31 K) via the two-halide pathway. Abstract: Reaction of 2-amino-5-trifluoromethylpyridine (5-TFMAP) with copper halides in water or alcohol solvents produced four coordination complexes: (5-TFMAP)2 CuX2, (X = Cl (1 ) or Br (2 )), (5-TFMAP)3 CuBr2 (3 ) and [(5-TFMAP)2 CuBr2 ](5-TFMAPH)Br (4 ). In all compounds, the 5-TFMAP ligands are coordinated to the Cu(II) ion through the pyridine nitrogen atom in a trans -geometry and a nearly square planar environment is observed in1, 2 and4 . In3, coordination of an additional 5-TFMAP ligand results in a distorted trigonal bipyramidal complex. All complexes are characterized by single-crystal X-ray diffraction. Compound1 crystalizes as a chain structure via pairs of long Cl…Cu contacts between molecules and the temperature dependent magnetic susceptibility data has been fit to an alternating chain model, resulting in J  = −5.97(1) K and J ′ = −0.95(4) K. Compound2 exhibits weaker antiferromagnetic interactions, also via the bihalide superexchange pathway, resulting in J  = −3.02(2) K from a fit to the uniform chain model. The structure of compound3 also exhibits a uniform antiferromagnetic chain, but via the two-halide pathway (short Br…Br contacts) and susceptibility data exhibit significantly stronger interactions ( J  = −31.05(5) K). Compound4 is not stable in air and loses a molecule of 5-TFMAP from the crystal lattice upon standing.